The Role of Mineral Deficiencies in Insulin Resistance and Obesity - Smita, Rafia M.; Shuvo, Anik P. R.; Raihan, Sabbir; Jahan, Rajib; Simin, Faria Anjum; Rahman, Ashiqur; Biswas, Soumick; Salem, Liyad; Sagor, Md. Abu Taher (Current Diabetes Reviews, 2022)
Minerals are critical for maintaining overall health. These tiny chemical compounds are responsible for enzymatic activation, maintaining healthy teeth and bones, regulating energy metabolism, enhancing immunity, and aiding muscle and brain function. However, mineral deficiency in the form of inadequate or under nourished intake affects millions of people throughout the world, with well-documented adverse health consequences of malnutrition. Conversely, mineral deficiency may also be a risk factor for Insulin Resistance (IR) and obesity. This review focuses on another, more “less discussed” form of malnutrition, namely mineral deficiency and its contribution to metabolic disorders. At the cellular level, minerals maintain not only molecular communication but also trigger several key biochemical pathways. Disturbances in these processes due to mineral insufficiency may gradually lead to metabolic disorders such as insulin resistance, pre-diabetes, and central obesity, which might lead to renal failure, cardiac arrest, hepatic carcinoma, and various neurodegenerative diseases. Here we discuss the burden of disease promoted by mineral deficiencies and the medical, social, and economic consequences. Mineral deficiency-mediated IR and obesity have a considerable negative impact on individual well-being, physical consideration, and economic productivity. We discuss possible molecular mechanisms of mineral deficiency that may lead to IR and obesity and suggest strategies to counter these metabolic disorders. To protect mankind from mineral nutrient deficiencies, the key is to take a variety of foods in reasonable quantities, such as organic and pasture-raised eggs, low fat dairy, and grass-fed and finished meats, insecticide, and pesticide-free vegetables and fruits.
Keywords: obesity